2016
DOI: 10.3350/cmh.2016.0048
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance and predictive factors of early massive recurrence after radiofrequency ablation in patients with a single small hepatocellular carcinoma

Abstract: Background/AimsRadiofrequency ablation (RFA) is one of the most frequently applied curative treatments in patients with a single small hepatocellular carcinoma (HCC). However, the clinical significance of and risk factors for early massive recurrence after RFA—a dreadful event limiting further curative treatment—have not been fully evaluated.MethodsIn total, 438 patients with a single HCC of size ≤3 cm who underwent percutaneous RFA as an initial treatment between 2006 and 2009 were included. Baseline patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 30 publications
5
22
1
Order By: Relevance
“…In previous studies assessing the risk factors for HCC recurrence, late recurrence (usually defined as tumor recurrence after 24 months) was related to underlying chronic liver disease, whereas early recurrence (usually defined as tumor recurrence within first 24 months) was associated with tumor-related factors (i.e., tumor size, tumor number, serum tumor marker, peripheral invasion, and vascular invasion) and treatment modality. [34][35][36][37][38][39][40] Consistent with those findings, our study also found that tumor factors or treatment modality were no longer independent factors for future HCC recurrence in HCC patients with 5 recurrence-free years while they were independent risk factors for HCC recurrence in the first 5 years.…”
Section: Discussionsupporting
confidence: 89%
“…In previous studies assessing the risk factors for HCC recurrence, late recurrence (usually defined as tumor recurrence after 24 months) was related to underlying chronic liver disease, whereas early recurrence (usually defined as tumor recurrence within first 24 months) was associated with tumor-related factors (i.e., tumor size, tumor number, serum tumor marker, peripheral invasion, and vascular invasion) and treatment modality. [34][35][36][37][38][39][40] Consistent with those findings, our study also found that tumor factors or treatment modality were no longer independent factors for future HCC recurrence in HCC patients with 5 recurrence-free years while they were independent risk factors for HCC recurrence in the first 5 years.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, we failed to show a statistically significant survival benefit of rifaximin in the HCC cohort, even after adjustment for treatment selection bias using inverse probability weighting based on propensity scores of the study patients. As is well‐known from previous studies Child‐Turcotte‐Pugh class and TNM stage were determined to be independent predictors for overall survival in the HCC cohort, suggesting that residual liver function and the tumour itself have profound impact on the prognosis of patients with HCC.…”
mentioning
confidence: 55%
“…Based on these results, we consider MR‐guided percutaneous tumor ablation as a feasible, safe, and accurate approach for the treatment of small hepatic tumors, which relies—to a large extent—on the reliable visualization of the target tumor and the applicator throughout the whole ablation procedure . This is of clinical relevance, as several studies reported that tumor size is an independent risk factor for local progression‐free survival and overall survival . Due to its high soft‐tissue contrast in combination with the possibility for multiplanar and real‐time imaging, MR image guidance is the modality of choice for small and difficult to reach target lesions, as it allows for precise planning, targeting, and immediate evaluation of treatment success .…”
Section: Discussionmentioning
confidence: 99%